Tata Rias dan Busana Tari Melaju dengan Mutu di Universitas PGRI Palembang - Bernika Muhlis Lasari; Hasan Hasan; Efita Elvandari (Abstrak : Jurnal Kajian Ilmu seni, Media dan Desain, 2024)
The Melaju With Quality dance is a dance that represents the PGRI Palembang University which has the motto "Melaju With Quality". Melaju With Quality Dance is a new dance creation created by Mrs. Rully Rochayati in 2017. Makeup is important in dance because it emphasizes the perfect parts of the face using the wahah corrective technique, this makes the dancer look more beautiful. The clothes worn by dancers in the Melaju With Mutu dance are blue and red shirts and trousers. This writing uses qualitative methods. The data collection process in this paper uses observation, interviews, documentation, literature study methods.